Perceptions of Mahu Land Communities About Rice and Sague In East Saparua District, Central Maluku District - Sahusilawane, Aphrodite M; Palembang, Septianti P (Tropical Small Island Agriculture Management, 2024)
Rice as a national food has contributed to all corners of the land in Maluku. Sago, which is usually present on the dining table, is now paired with rice. Research conducted in Mahu land’s Administrative, East Saparua District, Central Maluku Regency aims to determine the perceptions of people in Mahu land regarding rice and sago and how interested they are in eating sago in Mahu. The methods used are quantitative and qualitative with descriptive research characteristics. Primary data collection was carried out through observation, interviews, filling out questionnaires, FGD with stakeholders according to the research objectives. To determine strategic steps to increase interest in consuming sago, a SWOT analysis was used. The research results show that rice is an additional food, tends to be consumed by the younger generation, sago is still a staple food/main food.